2013
DOI: 10.1007/s10162-013-0429-5
|View full text |Cite
|
Sign up to set email alerts
|

Relearning Auditory Spectral Cues for Locations Inside and Outside the Visual Field

Abstract: Previous research has demonstrated that, over a period of weeks, the auditory system accommodates to changes in the monaural spectral cues for sound locations within the frontal region of space. We were interested to determine if similar accommodation could occur for locations in the posterior regions of space, i.e. in the absence of contemporaneous visual information that indicates any mismatch between the perceived and actual location of a sound source. To distort the normal spectral cues to sound location, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 54 publications
(53 reference statements)
2
44
0
Order By: Relevance
“…Previous work has demonstrated that listeners are able to recalibrate to new HRTFs following a relatively prolonged period of exposure Carlile et al, 2007;Carlile and Blackman, 2014;Majdak et al, 2013). Presumably the quality of that spatial information will be dependent on both the extent of the locationdependent changes and the uniqueness of the spectral profiles for each location.…”
Section: Blur Polar Anglementioning
confidence: 93%
See 2 more Smart Citations
“…Previous work has demonstrated that listeners are able to recalibrate to new HRTFs following a relatively prolonged period of exposure Carlile et al, 2007;Carlile and Blackman, 2014;Majdak et al, 2013). Presumably the quality of that spatial information will be dependent on both the extent of the locationdependent changes and the uniqueness of the spectral profiles for each location.…”
Section: Blur Polar Anglementioning
confidence: 93%
“…Previous studies have also demonstrated that when ear molds are worn continuously over a period of many days (10-60 days), subjects adapt to different degrees to the distorted HRTFs for spatial locations both within and outside the visual field (Carlile et al, 2007;Carlile and Blackman, 2014). These inter-subject differences in the time taken to adapt and the extent of the adaptation remain unexplained.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A number of more recent studies have examined the functional plasticity of the adult auditory system when localization cues are perturbed (ferrets: Kacelnik et al, 2006;humans: Van Wanrooij and Van Opstal, 2007;Kumpik et al, 2010;Carlile and Blackman, 2013; see also owls: Knudsen et al, 1994). Human subjects have also been shown to accommodate to some extent to perturbation of the monaural spectral cues in one ear only (Van Wanrooij and Van Opstal, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…12 To generate moving VAS stimuli, broadband noise (300 Hz to 16 kHz, 5 ms cosine ramps) was convolved with the transfer functions for successive horizontal positions (e.g., see Ref. 13).…”
Section: Stimulimentioning
confidence: 99%